Modulation of function of three ABC drug transporters, P-glycoprotein (ABCB1), mitoxantrone resistance protein (ABCG2) and multidrug resistance protein 1 (ABCC1) by tetrahydrocurcumin, a major metabolite of curcumin. - Limtrakul P. (2014)
Many studies have been performed with the aim of developing effective resistance modulators to overcome the multidrug resistance (MDR) of human cancers. Potent MDR modulators are being investigated in clinical trials. Many current studies are focused on dietary herbs due to the fact that these have been used for centuries without producing any harmful side effects. In this study, the effect of tetrahydrocurcumin (THC) on three ABC drug transporter proteins, P-glycoprotein (P-gp or ABCB1), mitoxantrone resistance protein (MXR or ABCG2) and multidrug resistance protein 1 (MRP1 or ABCC1) was investigated, to assess whether an ultimate metabolite form of curcuminoids (THC) is able to modulate MDR in cancer cells. Two different types of cell lines were used for P-gp study, human cervical carcinoma KB-3-1 (wild type) and KB-V-1 and human breast cancer MCF-7 (wild type) and MCF-7 MDR, whereas, pcDNA3.1 and pcDNA3.1-MRP1 transfected HEK 293 and MXR overexpressing MCF7AdrVp3000 or MCF7FL1000 and its parental MCF-7 were used for MRP1 and MXR study, respectively. We report here for the first time that THC is able to inhibit the function of P-gp, MXR and MRP1. The results of flow cytometry assay indicated that THC is able to inhibit the function of P-gp and thereby significantly increase the accumulation of rhodamine and calcein AM in KB-V-1 cells. The result was confirmed by the effect of THC on [(3)H]-vinblastine accumulation and efflux in MCF-7 and MCF-7MDR. THC significantly increased the accumulation and inhibited the efflux of [(3)H]-vinblastine in MCF-7 MDR in a concentration-dependent manner. This effect was not found in wild type MCF-7 cell line. The interaction of THC with the P-gp molecule was clearly indicated by ATPase assay and photoaffinity labeling of P-gp with transport substrate. THC stimulated P-gp ATPase activity and inhibited the incorporation of [(125)I]-iodoarylazidoprazosin (IAAP) into P-gp in a concentration-dependent manner. The binding of [(125)I]-IAAP to MXR was also inhibited by THC suggesting that THC interacted with drug binding site of the transporter. THC dose dependently inhibited the efflux of mitoxantrone and pheophorbide A from MXR expressing cells (MCF7AdrVp3000 and MCF7FL1000). Similarly with MRP1, the efflux of a fluorescent substrate calcein AM was inhibited effectively by THC thereby the accumulation of calcein was increased in MRP1-HEK 293 and not its parental pcDNA3.1-HEK 293 cells. The MDR reversing properties of THC on P-gp, MRP1, and MXR were determined by MTT assay. THC significantly increased the sensitivity of vinblastine, mitoxantrone and etoposide in drug resistance KB-V-1, MCF7AdrVp3000 and MRP1-HEK 293 cells, respectively. This effect was not found in respective drug sensitive parental cell lines. Taken together, this study clearly showed that THC inhibits the efflux function of P-gp, MXR and MRP1 and it is able to extend the MDR reversing activity of curcuminoids in vivo.